Komunikasi Di Era Digital: Analisis Media Konvensional Vs New Media Pada Kalangan Mahasiswa Ilmu Komunikasi Universitas Malikussaleh Angkatan 2021 - Ramadhana, Saskia Cahya; Hasan, Kamaruddin; Eni, Suci; Izzah, Nurul; Utami, Annisa (Universitas Gajah Putih, 2023)
In today's digital era, communication has undergone many changes, from the existence of conventional media to the convergence of media so that new media appears today. Along with the development of increasingly sophisticated technology, as well as easy access to new media, conventional media is slowly starting to compete. The students include users who are active in the use of digital media, how to use conventional media and new media in students of social sciences at university, and what are their critical responses to communication in the current digital era. The purpose of this study is to find out how the comparison of the use of communication in conventional media and new media occurs among Unimal 2021 communication science students. The research method used in this study is a qualitative method with descriptive elaboration, through data analysis techniques in the form of interviews and studies field (observation). The results of this study are shows that there are positive and negative impacts from the emergence of new media in the current digital era.